INTEGRASI PEMIKIRAN HEGEL DAN MARX DALAM PERSPEKTIF PSIKOANALITIK: STUDI KONSTRUKSI FILSAFAT SLAVOJ ŽIŽEK - Akbar, Muhammad; Adhimas Alifian Yuwono (CV. Denasya Smart Publisher, 2025)
This research aims to outline the integration of Georg Wilhelm Friedrich Hegel and Karl Marx's thoughts in Slavoj Žižek's philosophy through Jacques Lacan's psychoanalytic perspective. The main focus of the research is to understand how Žižek combines Hegel's dialectic that emphasises process, difference and contingency with Marx's materialism critique that has been considered too teleological, and enriches his analysis with Lacan's theory of the unconscious to answer contemporary socio-political issues more sharply and relevantly. The method used is a literature study by collecting data from books, journals, and trusted academic sources that discuss the thoughts of Žižek, Hegel, Marx, and Lacan. The data was analysed qualitatively with a descriptive and interpretative approach to explore the meaning and interrelationship of philosophical concepts in Žižek's philosophical construction. The results show that Žižek reconstructs Hegel's dialectic as an ontological foundation that emphasises contingency and uncertainty, while criticising the teleology of classical Marxism. He develops the concept of active and passive dialectical subjects, and uses Lacan's psychoanalysis to analyse ideology and the structure of subjectivity in modern capitalism. This approach results in a radical and applicable contemporary dialectical materialism, providing a framework for critical analysis of 21st century socio-political realities.